STUDI LITERATURE HUBUNGAN PENERAPAN KESADARAN KESEHATAN DAN KESELAMATAN KERJA (K3) DALAM MENINGKATKAN KINERJA KARYAWAN - Talitha Zulaika; Salianto, Nadila Chairani, Dina (CV. Adiba Aisha Amira, 2025)
This research uses a qualitative descriptive approach with literature study to understand the application of K3 relationships to employee performance. The data taken is based on reviewed articles using the keywords implementation of occupational health and safety (K3) on employee performance. The research results show that there is a link between the implementation of occupational health and safety awareness on employee performance levels. Apart from being a moral necessity for the business world, creating a safe and healthy work environment is also important for increasing employee productivity. Worker health problems or injuries resulting from neglect of K3 can significantly affect employee performance. When workers perform well, the company can achieve its goals as best as possible. K3 is now mandatory for all employees and helps fulfill work, comprehensive employee health and safety insurance, freeing workers from physical and emotional suffering.